2023
DOI: 10.1155/2023/7965735
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Potential Roles of Branched-Chain Amino Acids in the Regulation of Muscle Growth in Common Carp (Cyprinus carpio) Based on Transcriptome and MicroRNA Sequencing

Abstract: Branched-chain amino acids (BCAAs) can be critically involved in skeletal muscle growth and body energy homeostasis. Skeletal muscle growth is a complex process; some muscle-specific microRNAs (miRNAs) are involved in the regulation of muscle thickening and muscle mass. Additionally, the regulatory network between miRNA and messenger RNA (mRNA) in the modulation of the role of BCAAs on skeletal muscle growth in fish has not been studied. In this study, common carp was starved for 14 days, followed by a 14-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The transcriptome provides a useful method for exploring genetic information. Relying on the transcriptome can yield insights into growth differences [4][5][6]29]. This study identified a noticeable growth difference, along with an evident transcriptome distinction.…”
Section: Differences In the Metabolism Pathwaysmentioning
confidence: 89%
“…The transcriptome provides a useful method for exploring genetic information. Relying on the transcriptome can yield insights into growth differences [4][5][6]29]. This study identified a noticeable growth difference, along with an evident transcriptome distinction.…”
Section: Differences In the Metabolism Pathwaysmentioning
confidence: 89%
“…Increased calcium levels lead to elevated MYLK activity, resulting in myosin light chain phosphorylation and muscle contraction. [ 26 ] This process is extensively involved in the regulation of smooth muscle, such as in the contraction and relaxation of vascular smooth muscle. MYLK’s function is not only vital in normal physiological processes but also plays a role in disease development.…”
Section: Discussionmentioning
confidence: 99%